The Effect of Commitment to Managerial Performance Intervening Variable at the National Baznas of Riau Province - Yusrawati; Mariyanti, Tatik; Septiani, Nanda (Aptisi Transactions On Technopreneurship (ATT), 2022)
The world has entered the digital era 4.0. Zakat and infaq are the drivers of economic improvement. This is because zakat and infaq funds are a source of funds for the community. Internal control is very necessary because good internal control is a reflection of good managerial practices. In order to maintain good trust, good managerial practices, one of which is through the existence of an internal control system. The company is expected to pay attention to human resources or employees by understanding the factors that can support employee performance. This study uses research design methods and data analysis methods. The aim is to empirically test the effect of internal control on accountability and management at BAZNAS Riau Province. Thus, it is hoped that the distribution of zakat, infaq, and appropriate funds can break the chain of poverty caused by income. Internal control is very necessary.